Curriculum evaluation of French learning in senior high school - Irma Nur Af'idah; Amat Jaedun (REID (Research and Evaluation in Education), 2020)
The research aims to describe the implementation of French language learning in high schools of Sleman Regency viewed from the components of planning, implementation, and results. This evaluation research uses a quantitative descriptive approach with a countenance model from Stake. Respondents in this research were teachers and students at three senior high schools. Data collection techniques used in this study include research lesson plans, questionnaires, and documentation. The results of this research indicate that: (1) in the planning component, the quality of lesson plan preparation is very good and needs to be maintained because in the lesson plan review, the results obtained are 88.9% and the teacher questionnaire results of 26.6 are included in the excellent category; (2) in the implementation component, it has good results with the acquisition of a total score of 77 and a student questionnaire of 66.19; (3) in the component of the results, good results are obtained with an average value of students that is 86.38 and the results of the teacher questionnaire of 65.7 which is above 61 so that it falls into the good category. Student scores are obtained from the results of the middle semester assessment and teacher questionnaire.